SITUS BAGELEN SEBAGAI SUMBER BELAJAR IPS DI SMP N 7 PURWOREJO (Harmony: Jurnal Pembelajaran IPS dan PKN, 2019)
The purpose of this study was 1) to know the learning process by utilizing the Bagelen Purworejo Site as a source of social studies learning for students of class VII students in 7 Purworejo Junior High School, 2) knowing the obstacles faced by teachers and students in utilizing the Bagelen Purworejo Site as a source of social studies learning, and 3) know the response of students after visiting the Bagelen Purworejo Site. This research was conducted with a qualitative-narrative framework. The results of this study indicate, 1) social studies learning outside the classroom using the model of a small historian, namely students acting as historians who try to observe historical sites and record some important things, such as the history of the site and the values ​​that can be learned; 2) the main obstacle for teachers is on the internet network, it is quite disturbing to use Youtube as a source of supporting information in learning; and 3) students positively appreciate the learning that takes place, for students such learning makes the learning atmosphere more creative and enjoyable. Tujuan penelitian ini adalah 1) mengetahui proses pembelajaran dengan memanfaatkan Situs Bagelen Purworejosebagai sumber belajarIPS untuk siswa kelas VII SMP N 7 Purworejo, 2) mengetahui kendala-kendala yang dihadapi guru dan siswa dalam memanfaatkan Situs Bagelen Purworejo sebagai sumber belajar IPS, dan 3) mengetahui respon siswa setelah melakukan metode kunjungan ke Situs Bagelen Purworejo.Penelitian ini dikerjakan dengan kerangka kualitatif-naratif. Hasil penelitian ini menunjukkan, 1) pembelajaran IPS di luar kelas menggunakan model sejarawan kecil, yaitu siswa bertindak sebagai sejarawan yang mencoba mengamati situs bersejarah dan mencatat beberapa hal yang penting, seperti sejarah situs itu dan nilai yang dapat dipelajari; 2) kendala utama guru adalah pada jaringan internet, hal itu cukup mengganggu penggunaan media Youtube sebagai sumber informasi pembantu dalam pembelajaran; dan 3) siswa mengapresiasi secara positif pembelajaran yang berlangsung, bagi siswa pembelajaran semacam itu membuat suasana belajar lebih rekreatif dan menyenangkan.